3D Printing Bioinspired Ceramic Composites. Issue 1 (December 2017) - Feilden, Ezra; Ferraro, Claudio; Zhang, Qinghua; García-Tuñón, Esther; D'Elia, Eleonora; Giuliani, Finn; Vandeperre, Luc; Saiz, Eduardo
Abstract Natural structural materials like bone and shell have complex, hierarchical architectures designed to control crack propagation and fracture. In modern composites there is a critical trade-off between strength and toughness. Natural structures provide blueprints to overcome this, however this approach introduces another trade-off between fine structural manipulation and manufacturing complex shapes in practical sizes and times. Here we show that robocasting can be used to build ceramic-based composite parts with a range of geometries, possessing microstructures unattainable by other production technologies. This is achieved by manipulating the rheology of ceramic pastes and the shear forces they experience during printing. To demonstrate the versatility of the approach we have fabricated highly mineralized composites with microscopic Bouligand structures that guide crack propagation and twisting in three dimensions, which we have followed using an originalin-situ crack opening technique. In this way we can retain strength while enhancing toughness by using strategies taken from crustacean shells.